New record of Schizophyllum (Schizophyllaceae) from Mexico and the confirmation of its edibility in the humid tropics - Carreño-Ruiz, Santa D.; Lázaro, Abisag A. Ávalos; García, Silvia Cappello; Hernández, Rigoberto Gaitán; Chen, Jie; Navarro, Griselda K. Guillén; Fajardo, Luz V. García; Pérez, Nelly Del C. Jiménez; Cruz, Magdiel Torres De La; Blanco, Joaquín Cifuentes; Cappello, Renato E. (Phytotaxa, 2019)
The genus Schizophyllum is easily recognized within the order Agaricales. However, at the species level, taxonomic information for identification purposes is limited. The objective of the present study was to confirm the identity of the Schizophyllum species present in Tabasco, Mexico, by means of a detailed taxonomic revision of the macro- and micromorphological characters in more than 90 specimens, as well as phylogenetic analyses inferred from ITS sequence data. In total, three Schizophyllum species are described, of which one constitute a new record for Mexico. Finally, the edibility of S. radiatum is reported for the first time in the humid tropical region.